The Relationship Between Wrist Flexibility, Arm Muscle Strength, and Arm Explosive Power on Lob Shot Ability in Badminton - Ishak, Muhammad; Sahabuddin, Sahabuddin; Sudirman, Sudirman (Sains Global Institut, Indonesia, 2024)
This study aims to determine; 1) Want to know the relationship between wrist flexibility and lob shot ability in badminton. 2) Want to know the relationship between arm muscle strength and lob shot ability in badminton? 3) Want to know the relationship between arm explosive power and lob shot ability in badminton? 4) Want to know the relationship between wrist flexibility, arm muscle strength, and arm explosive power together on the ability to hit lobs in badminton among Watansoppeng 1 Public High School students? The population is students of Watansoppeng 1 Public High School. The sample used was 60 male students. The sampling technique is to use a simple random sampling technique. The variables involved in this research are the independent variables' physical condition and lob-hitting ability. The test instruments used were physical conditions consisting of wrist flexibility, arm muscle strength, and arm explosive power, while the ability to hit a lob by smashing 10 times. The data analysis techniques used are descriptive analysis and analytical analysis. The research results concluded that; (1) There is a significant relationship between wrist flexibility and lob ability in badminton, (2) There is a significant relationship between arm muscle strength and lob ability in badminton, (3) There is a significant relationship between arm explosive power and lob ability. in badminton, and (4) There is a significant relationship between wrist flexibility, arm muscle strength, and arm explosive power on lob shot ability in badminton.